Obsidian ASG autologous platelet-rich fibrin matrix for the prevention of postoperative pancreatic fistula following pancreatic resection: study protocol for a feasibility trial at the Medical University of Vienna - Ulla Klaiber; Oliver Strobel; Martin Schindl; Charlotte Gustorff; Christopher Dawoud; Carl-Stephan Leonhardt; Stefan Riss; Klaus Sahora (BMJ Open)
Introduction Postoperative pancreatic fistula (POPF) is the most frequent complication after partial pancreatectomy, which is by definition associated with clinical consequences requiring changes in postoperative management. Despite numerous scientific efforts, effective procedures to prevent POPF are lacking. Obsidian ASG autologous platelet-rich fibrin matrix has been effectively applied to prevent anastomotic leakage following colorectal surgery. This study is the first to investigate the feasibility of using the sealant in pancreatic surgery.Methods and analysis 25 consecutive patients scheduled for elective formal partial pancreatectomy due to any underlying disease fulfilling the eligibility criteria will be included. Obsidian ASG sealant prepared out of 120 mL of each patient’s whole blood will be applied to the pancreatic stump or the pancreatic anastomosis, respectively. The primary endpoint is the feasibility of the procedure, for example, the proportion of patients undergoing successful trial intervention. Secondary endpoints comprise safety and surgical outcome parameters including rate and severity of POPF as well as further pancreas-specific complications as defined by the International Study Group of Pancreatic Surgery during 90 days after surgery. Patients will be matched with a historic collective in a 1:2 ratio to gain first data on efficacy.Ethics and dissemination This trial and the associated study protocol (V.1.1.1, date 26 March 2024) were approved by the institution’s ethics committee (reference number 2191/2023). All trial procedures are performed in accordance with the International Council for Harmonisation harmonised tripartite guideline on Good Clinical Practice and the ethical principles of the Declaration of Helsinki. After completion of the study, results will be published in due course.Trial registration number The trial was registered in the German Clinical Trials Register on 6 May 2024 (DRKS-ID: DRKS00034052).